The Causality of BI Rate and Federal Fund Rate - Andrian Dolfriandra Huruta (Jurnal Keuangan dan Perbankan, 2018)
The Central Bank held power to carry out a monetary policy through the setting of monetary targets such as the money supply or interest rates with the main objective of maintaining inflation at the level determined by the government. At the operational level, this monetary objective depends on the use of instruments, including open market operations in the foreign exchange market, the setting of the discount rate, the setting of minimum reserve requirements and regulating credit or financing. We analyzed the causality of Bank Indonesia (BI Rate) and US interest rates (Federal Fund Rate). This study used secondary data, especially data from Bank Indonesia and The Federal Reserve. This data was the ones from the monthly time series from January 2006 to May 2016. This study used Granger causality test to determine the causality of BI Rate and Federal Fund Rate. Granger Causality test results indicated that there was no causality between the BI Rate and the Federal Fund Rate. We found that the movement of interest rates was not only caused by the external side, but also by the internal side. The case in Indonesia showed that the movement of interest rates was mainly due to an increase in gross domestic product, low participation in the Global Value Chain and the adoption of the expansionary monetary policy.JEL Classification: E43, E52, E58DOI: https://doi.org/10.26905/jkdp.v22i3.1972